PENGARUH STRES KERJA, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA PT. KUNANGO JANTAN KAMPAR - Zahara Meilan Fara; Raden Raden; Taufiq Taufiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine whether work stress, organizational culture and job satisfaction have a significant influence on turnover intention of employees of PT. Kampar male kunango. The population in this study includes all employees at PT. Kampar Male Kunango. Primary data was collected by using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using multiple regression with the help of the SPSS program. The sample collection technique that has been selected is the solvin formula (115 employees at PT. Kunango Jantan Kampar). The results showed that job stress, organizational culture and job satisfaction simultaneously had a significant effect on turnover intention, job stress had a significant effect on turnover intention, organizational culture had a significant effect on turnover intention, and job satisfaction had no significant effect on turnover intention.keywords: job stress, organizational culture, job satisfaction, turnover intention